Peranan Bimbingan Konseling Dalam Etis Teologis Untuk Menanggulangi Pergaulan Bebas Pada Remaja - Kornelia Yess Fibrianti; Yesa Cinta; Kristiani Kristiani (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
This study describes the role of ethical, theologically based counseling in overcoming promiscuity among teenagers. Promiscuity, which is becoming a social phenomenon that is increasingly widespread in society, is influenced by various internal and external factors that have a negative impact on the physical, mental health and academic achievements of teenagers. Through a descriptive qualitative method approach, the researcher explains theoretically and practically about promiscuity with the role of guidance and counseling in overcoming promiscuity ethically and theologically using a literature study approach and by collecting existing data and facts that occur in the field related to information. in discussing the theme, based on appropriate and appropriate reading references which form the basis for explaining the role of counseling guidance in theological ethics to overcome promiscuity. This approach also involves collaboration between counselors, families, and religious institutions to create an environment conducive to the moral and spiritual development of adolescents. The results show that applying this approach can be a holistic solution in facing the challenges of promiscuity among the younger generation.